Effect of Medium Formulation and Culture Condition on Growth and Plasmid Stability of Recombinant Lactococcus Lactis AM3 - Ho, Hooi Ling (2002)
Chicken Anemia Virus (CAV) is a small spherical negative single stranded DNA virus which comprised of several overlapping open reading frames (ORPs), three of which encoded for the proteins size of 52, 24 and 13 kDa, designated as VPl, VP2 and VP3, respectively. The recombinant Lactococcus lactis AM3 used in the study was transformed with a plasmid expression vector, pMG36e, which was cloned with the VP3 gene of CAV. This recombinant Lactococcus lactis AM3 was constructed as a model to study the possibility of vaccine delivery into the poultry via oral route. The investigation on the growth of the recombinant Lactococcus lactis AM3 in different carbon sources (glucose, sucrose, lactose and xylose) showed that glucose was the most suitable carbon source where it successfully produced 36; generation numbers of bacteria with final plasmid-bearing cells, 1.13 X 1017 cfu.L⁻¹ after 24 hours of fermentation. The final plasmid stability of recombinant Lactococcus lactis AM3 grew in the glucose medium was 98% indicating that most of the recombinant bacterial still retained their plasmids. There was a stable and optimum growth of the recombinant Lactococcus lactis AM3 in the culture medium with 10 g.L⁻¹ of glucose concentration. The maximum'specific growth rate of plasmid-bearing cells in the culture, .µMAXpb was 0.9885h⁻¹. The higher concentration of glucose (20, 40 and 60 g.L⁻¹) in the medium inhibited the growth of recombinant Lactococcus lactis AM3 . The specific growth rate of Lactococcus lactis AM3 grew in the medium with 20 g.L⁻¹ of yeast extract was the highest, 0.8869 h⁻¹ with 84% of plasmid stability. Similar polypeptides average molecular weights are observed in the yeast extract medium that increased the nitrogen consumption by the recombinant bacteria and eventually increased the bacteria cell number. Further experiments confirmed that 20 g.L⁻¹ of glucose and 20 g.L-1 of yeast extract containing medium was the optimum carbon-nitrogen source for the growth and plasmid maintenance of the recombinant Lactococcus lactis AM3. The specific growth rate and plasmid stability of Lactococcus lactis AM3 in this complex medium were increased to 1.6304 h⁻¹ and 87%, respectively after 26 hours of batch fermentation. There was no nitrogen deficiency occurred and the lost of plasmid, pMG36e-VP3 from the host cell was caused majority by the segregational instability of plasmid after prolonged fermentation. The specific growth rate of recombinant Lactococcus lactis AM3 grew at pH medium 6.5 was the highest, 1.0227 h⁻¹. 91% of plasmid stability of recombinant Lactococcus lactis AM3 grew at pH 6.5 was observed. The maximum specific growth rate of Lactococcus lactis AM3 grew at 30‹C was 0.9780 h⁻¹ with total plasmid-bearing cells of 9.80 X 1020 cfu.L⁻¹ after 28 hours of fermentation. Similar acid-inducible proteins were produced by recombinant Lactococcus lactis AM3 when confronted with high temperatures (32, 34, 36 and 38˚c%). 90% of plasmid stability was observed in Lactococcus lactis AM3 grew at 30‹C. Recombinant Lactococcus iactis AM3 grew in the MRS medium that agitated with 200 r.p.rn. produced 32 generations of plasmid..bearing cells, 3.87 X 1 019 cfu.L⁻¹ with 51% of plasmid stability after 26 hours of fermentation. Obvious fluctuation of the plasmid stability of pMG36e- VP3-bearing cells was observed during the batch fermentation system. The appearance of adaptive descendants without plasmids derived from the bacterial host cells was detected throughout the experiments. The lost of plasmid, pMG36e- VP3 from recombinant Lactococcus lactis AM3 and the fluctuations in the population of plasmid..losing cells in the batch fermentation system suggested that the presence of antibioticdegraded proteins or acids were produced from the bacterial host cells that responsible in the inhibition of proper function of erythromycin in the culture. Most of the plasmid instability was caused by segregational instability.